PEMANFAATAN KOTORAN KAMBING SEBAGAI PUPUK ORGANIK UNTUK MENINGKATKATKAN KEBERSIHAN LINGKUNGAN DI DESA MOJOSARI - Sugito, Sugito; Khoirin, Lukman (Abdimas IAI Ngawi, 2024)
The problem that will be revealed is how to manage goat manure, which was originally a waste in the environment, can be used as organic fertilizer which has proven to be very good in improving the structure of agricultural soil. Sources of organic matter can be in the form of compost, green manure, and manure. Organic fertilizers in the manufacture of manure in the form of nutrients are relatively high because goat manure is mixed with urine (urine) which also contains nutrients. The main purpose of this community service activity is to provide insight and knowledge and promote the management of goat manure into organic fertilizer to clean the surrounding environment because it is free from goat manure waste. Real work lecture activities for the community for residents of the Mojosari village have been carried out from 1 to 30 August 2022 with the theme ABCD (Asset Based Community-Driver Development). The training materials are provided in various forms, namely lectures, questions and answers, practice of making compost. The texture of goat manure is very distinctive because it is in the form of granules which are rather difficult to break down physically so that it greatly affects the decomposition process and the process of providing nutrients. Training in organic fertilizer production from goat manure has various benefits, including reducing waste accumulation and improving environmental cleanliness. Additionally, this training can decrease the unemployment rate in the Mojosari and Kepobar districts, as well as enhance the skills and income of the local community.   Abstrak : Permasalahan yang muncul adalah apa yang harus dilakukan dengan kotoran kambing yang semula dibuang ke lingkungan, namun dapat dimanfaatkan sebagai pupuk organik dan terbukti sangat baik dalam memperbaiki struktur tanah pertanian. Sumber bahan organik antara lain kompos dan sayuran. Kotoran kambing juga bisa dijadikan bahan. Kotoran kambing yang bercampur dengan urin yang juga mengandung unsur hara membuat pupuk organik berupa pupuk kandang relatif bergizi. Tujuan utama dari organisasi nirlaba ini adalah untuk memberikan wawasan dan pengetahuan serta menggalakkan pengolahan kotoran kambing menjadi pupuk organik untuk membersihkan lingkungan karena bebas kotoran kambing. Kegiatan kursus praktik komunitas ABCD (Asset Based Community-Driver Development) bagi warga Kecamatan Mojosari. Materi pelatihan diberikan dalam berbagai format, antara lain ceramah, tanya jawab, dan latihan pembuatan pupuk kompos. Tekstur kotoran kambing sangat khas karena berbentuk butiran dan sulit terurai secara fisik sehingga berdampak besar pada proses dekomposisi dan  penyediaan unsur hara. Pelatihan produksi pupuk organik dari kotoran kambing memiliki berbagai manfaat, antara lain mengurangi timbunan sampah dan meningkatkan kebersihan lingkungan. Selain itu, pelatihan ini dapat mengurangi tingkat pengangguran di Kecamatan Mojosari dan Kepobar, serta meningkatkan keterampilan dan pendapatan masyarakat setempat. Kata Kunci : kotoran kambing; pupuk organik; kebersihan lingkungan.